Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) untuk Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik Kelas XI MIPA 5 Semester 1 Materi Trigonometri di SMA Negeri 1 Godong - Septin Rini Indrawati (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The application of the Numbered Heads Together (NHT) Cooperative Learning model to increase the activity and learning outcomes of Class XI MIPA 5 Students on Trigonometry at SMA Negeri 1 Godong in the Academic Year 2022/2023. The background of this research is that mathematics as one of the lessons in school plays quite a role important in forming quality students, because mathematics is a means of thinking to examine everything logically and systematically. Therefore, it is necessary to improve the quality of education in mathematics. One of the things that must be considered is the improvement of students' mathematics learning outcomes at school. This research is a Classroom Action Research (PTK) which is carried out collaboratively. The subjects of this study were 36 students of class XI MIPA 5 at SMA Negeri 1 Godong. The research object was the implementation of learning mathematics with the NHT (Numbered Heads Together) learning model to determine student activity and achievement. In this study, it consisted of 2 cycles, namely cycle I, three meetings and cycle II, three meetings. Research data obtained from observations during learning activities , questionnaire results, test results and documentation.The data analysis technique used is descriptive qualitative method and to calculate the data using quantitative methods.The results of this study indicate that student activity has increased, as seen from the activeness questionnaire, for the first cycle of the 1st meeting the percentage was 65.36 % and at the second meeting it increased to 71.79%, so that in the first cycle it reached 68.57%. 50%.In addition, you can also see an increase in activity from the observation sheet, the activity of each indicator has increased. Students also experienced an increase, in the first cycle of the student evaluation test results the average value was 68.75, students who fulfilled the KKM with a percentage of 65% (15 students who completed) increased in cycle II with a percentage of 78% (31 students who completed ) which fulfilled the KKM with an average of 79.58.